COVID-19 and UK family carers: policy implications. (October 2021) - Onwumere, Juliana; Creswell, Cathy; Livingston, Gill; Shiers, David; Tchanturia, Kate; Charman, Tony; Russell, Alisa; Treasure, Janet; Di Forti, Marta; Wildman, Emilie; Minnis, Helen; Young, Allan; et al.
Summary: Informal (unpaid) carers are an integral part of all societies and the health and social care systems in the UK depend on them. Despite the valuable contributions and key worker status of informal carers, their lived experiences, wellbeing, and needs have been neglected during the COVID-19 pandemic. In this Health Policy, we bring together a broad range of clinicians, researchers, and people with lived experience as informal carers to share their thoughts on the impact of the COVID-19 pandemic on UK carers, many of whom have felt abandoned as services closed. We focus on the carers of children and young people and adults and older adults with mental health diagnoses, and carers of people with intellectual disability or neurodevelopmental conditions across different care settings over the lifespan. We provide policy recommendations with the aim of improving outcomes for all carers.